Long Noncoding RNA X-Inactive-Specific Transcript Promotes the Secretion of Inflammatory Cytokines in LPS Stimulated Astrocyte Cell Via Sponging miR-29c-3p and Regulating Nuclear Factor of Activated T cell 5 Expression - Zhang, Mengqi; Yang, Haojun; Chen, Zhuohui; Hu, Xinhang; Wu, Tong; Liu, Weiping (Frontiers in Endocrinology, 2021)
Background: Astrocyte activation promotes glutamate accumulation and secretion of inflammatory factors, mainly responsible for epilepsy. Long noncoding RNA (lncRNA) X-inactive-specific transcript (XIST) regulates inflammation; however, the biological role and regulatory mechanism of XIST during astrocyte activation remain unclear. Methods: In the present study, rat epilepsy model and lipopolysaccharide (LPS)-treated CTX-TNA2 were established. XIST and miR-29c-3p expression were evaluated using quantitative real-time polymerase chain reaction. Nuclear factor of activated T cells 5 (NFAT5) was measured using western blot analysis. Interleukin (IL)-1β, IL-6, tumor necrosis factor-α, and L-glutamate levels in the culture supernatants were assessed using enzyme-linked immunosorbent assay. The binding between XIST and miR-29c-3p and between miR-29c-3p and the 3′-UTR of NFAT5 was analyzed using dual-luciferase reporter, RNA-binding protein immunoprecipitation (RIP), and Biotin pull-down assay. The proliferation and apoptosis were evaluated using CCK8 and flow cytometry, respectively. Results: XIST expression and NFAT5 protein level was increased, whereas miR-29c-3p expression was decreased in the epilepsy rat model and LPS-treated CTX-TNA2 cells. Silenced XIST expression, miR-29c-3p overexpression, or silenced NFAT5 expression inhibited the secretion of IL-1β, IL-6, and TNF-α and promoted glutamate transport in LPS-treated CTX-TNA2 cells. miR-29c-3p was the potential miRNA sponged by XIST. NFAT5 acted as a direct binding target of miR-29c-3p. Silenced miR-29c-3p expression or NFAT5 overexpression reversed the effect of silenced XIST expression on LPS-treated CTX-TNA2.XIST and miR-29c-3p treatment does not affect NFAT5 mRNA expression, but affects NFAT5 protein level. Furthermore, underexpressed XIST or overexpressed miR-29c-3p in LPS-stimulated CTX-TNA2 can attenuate neuronal apoptosis induced by LPS-stimulated CTX-TNA2. Conclusion: LncRNA XIST promotes the secretion of inflammatory cytokines in LPS- treated CTX-TNA2 via sponging miR-29c-3p and regulating NFAT5 expression.